Handbook of fat replacers - Roller, Sibel (CRC Press LLC, 2011)
Technology is only beginning to catch up with the public demand for foods that are low in fat and taste good. An extensive number of ingredients are under development for the sole purpose of fat replacement, using a variety of approaches and base materials. The Handbook of Fat Replacers describes in detail, for the first time in a single volume, the science and application of fat replacers in food products, including the multiplicity of technological, legislative, sensory, nutritional, and marketing issues involved.Information for each ingredient includes:o its history and use as a fat replacero production processo chemical structure and functional propertieso interactions with other food ingredientso nutritional, toxicological, and legal status of its useo selected examples of food product formulations